Lastros de um passado industrial e ferroviário em Fortaleza: o patrimônio cultural edificado das "Oficinas do Urubu" - Façanha, Tainah Rodrigues (2022)
Modernization processes, such as industrial and railway activities, have faced, in certain places, the decline of their operations and, with this, it is observed that there is an architectural legacy in a situation of obsolescence. These buildings have bec ome isolated fragments of contemporary urban life and, when segregated or abandoned, result in negative impacts on their landscapes in the form of urban voids and underutilized spaces. Such situation is also the result of a conscious negligence on the part of the agents involved, regarding preservation, conservation and reuse practices, since they occupy large idle areas, which are the focus of real estate speculation and urban densification. This is the case, in Fortaleza, of its first industrial area to t he west of the city which, consolidated in the early twentieth century, along with the development of the railroads, has undergone numerous transformations until the 1970s, when such activities went into decline. We propose, therefore, an analysis of this area of the city and of the object of study which is a complex of railway workshops located therein, the Oficinas da Rede de Viação Cearense, also known as Oficinas do Urubu, built in the 1930s to support the railroads. This research aims to understand, fr om a historical and critical perspective, the railway complex of Oficinas do Urubu, considering both its relationship with the industrial activity and the railways of Fortaleza, in addition to its current state of conservation, its relationship with the su rroundings and its heritage value as a ballast of the industrial and railway past of Fortaleza. The most significant time frame refers, mainly, to the period between 1920 and the mid 1970s, regarding its unfoldings nowadays. To this end, the research metho dology includes: a bibliographical survey, based on secondary sources, documents and iconography for historical and conceptual analysis; and an in loco study for architectural analysis and characterization of the workshops and their surroundings, with the workshops being the main primary source of research, both in its material aspects the building and its immaterial aspects social and cultural relations associated with it. In this sense, we present, at first, a historiographic perspective on the indu strial and railway past of Fortaleza; then, the analysis of the workshops and their surroundings, both from the architectural point of view and the current situation of the set and its surroundings; finally, we address the issue of cultural heritage and it s respective values, from a theoretical and critical point of view, including the considerations of the population involved. In this way, we approach the possibilities of a dialogue between the railway industrial heritage and the daily practices that give meaning to the city.